The promise of cinema : German film theory, 1907--1933 - Kaes, Anton; Baer, Nicholas, 1985-; Cowan, Michael J., 1971- (University of California Press, 2016)
Rich in implications for our present era of media change, The Promise of Cinema offers a compelling new vision of film theory. The volume conceives of "theory" not as a fixed body of canonical texts, but as a dynamic set of reflections on the very idea of cinema and the possibilities once associated with it. Unearthing more than 275 early-twentieth-century German texts, this ground-breaking documentation leads readers into a world that was striving to assimilate modernity's most powerful new medium. We encounter lesser-known essays by Béla Balázs, Walter Benjamin, and Siegfried Kracauer alongs.
Keywords: Motion pictures -- Germany -- History -- 20th century.; Film criticism -- Germany.; Motion pictures -- History -- 20th century.; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Critique cinématographique -- Allemagne.; Cinéma -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- General.; Film criticism; Motion pictures; Germany; Filmtheorie; 1900-1999; History